Aplikasi Penyemprotan Perasan Daun Kamboja (Plumeria acuminata) Terhadap Kematian Lalat Rumah (Musca domestica) - Vina Yuliana; Yamtana Yamtana; Abdul Hadi Kadarusno (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2016)
Abstract: Spraying application leaf squeeze kamboja (plumeria acuminata) to death fly house (musca domestica). Housefly (Musca domestica) is a vector for transmission of various types of mechanically transmitted diseases such as diarrhea, dysentery, cholera, typhoid, salmonellosis and viral gastrointestinal diseases. One of the control flies using environmentally friendly plant-based insecticides. Researchers used insecticides in the form of freshly squeezed vegetable leaf with frangipani (Plumeria acuminata). The objective was to knowing the influence of leaf squeeze spraying frangipani with a concentration of 40 percent, 50 percentand and 60 percent of the death house fly. This study uses experimental design With Post Test Only Control Group Design. The object of this study is the 480 flies were obtained from the TPS Market Tlagareja. This research was carried out by spraying the leaf squeeze frangipani at a concentration of 40%, 50% and 60%. Counting the number of deaths house fly performed after 24 hours. The results of this research are there meaningful influence of sraying the frangipani leaf squeeze againts the death house flies and the value of sig 0,000. Concentration of 40%, 50%, and 60% respectively can be deadly flies an average of 5 tails, 10 tails and 15 tails. The most effective concentration was 60% obtained from the LSD test with significance level of 0.000 and Different Mean values (IJ) is the largest 10.00000. The conclusion is an effect spraying frangipani leaf squeeze with a concentration of 40%, 50%, and 60% of the death house fly. The most effective concentration to kill flies is at 60%, with an average mortality of flies 15 tails. Keywords: frangipani leaf, house flies, insecticide plant